2009
DOI: 10.1097/aln.0b013e318191693a
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Continuous Infusion versus  Automated Bolus for Postoperative Patient-controlled Analgesia with Popliteal Sciatic Nerve Catheters

Abstract: In continuous popliteal sciatic block, local anesthetic administered as an automated regular bolus in conjunction with PCA provided similar pain relief as a continuous infusion technique combined with PCA; however, the new dosing regimen reduced the need for additional PCA and the overall consumption of local anesthetic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 24 publications
(16 reference statements)
4
66
2
Order By: Relevance
“…2–4). This might be viewed as a positive finding if the sensory block—and, therefore, possibly analgesia—was greatly increased in the bolus-only group, in line with previous reports of continuous popliteal-sciatic nerve blocks 12,22. Unfortunately, this was not the case: tolerance to cutaneous electrical current was virtually indistinguishable at Hour 6 between the two groups (fig.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…2–4). This might be viewed as a positive finding if the sensory block—and, therefore, possibly analgesia—was greatly increased in the bolus-only group, in line with previous reports of continuous popliteal-sciatic nerve blocks 12,22. Unfortunately, this was not the case: tolerance to cutaneous electrical current was virtually indistinguishable at Hour 6 between the two groups (fig.…”
Section: Discussionsupporting
confidence: 86%
“…The first is in catheter-insertion methodology: the previous studies used nerve stimulation to guide needle placement, but then “blindly” advanced nonstimulating catheters 4–5 cm past the needle tip 12,22. As the previous investigators noted, “the final location of the catheter tip… may have actually been located distant from the targeted nerve… This may render it difficult, or even impossible, for the local anesthetic to traverse the distance between the tip and the two sciatic nerve trunks when a slow continuous infusion with an overall small volume is used… In contrast, the use of an intermittent bolus is accompanied by higher pressure and more volume per time, which may increase the spread of local anesthetic…”12 In contrast, our current study used ultrasound to allow positioning of the catheter tips at a precise (and bilaterally equivalent) location immediately posterolateral to the femoral nerve, resulting in very accurate perineural local anesthetic deposition and possibly improved nerve-anesthetic contact.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that sequential epidural boluses improve the quality of sensory blockade as compared with a continuous epidural block 6. Similarly, Taboada et al found that local anesthetic administered during a continuous popliteal block as a programmed bolus provided similar pain relief, and reduced the need for PCA, as well as demonstrating a decrease in overall consumption of local anesthetic 7. However, little information is available to compare the analgesic effect of PIBI in combination with PCA versus CI in combination with PCA during a continuous thoracic PVB.…”
Section: Introductionmentioning
confidence: 99%
“…6 The minimum sample size required was 34 patients per group for a power of 90% with a 2-tailed significance level of 5% (β = 0.1 and α = 0.05). We therefore decided to enroll 101 patients, 50 in the continuous infusion group and arbitrarily 51 in automated bolus group to allow for possible dropouts.…”
Section: Sample Sizementioning
confidence: 99%
“…Compared with continuous infusion, an intermittent bolus regimen has been shown to reduce local anesthetic consumption and improve analgesia in continuous sciatic 6 and epidural blockade. 7 There has been little investigation into the influence of method of local anesthetic delivery on pain relief and adverse effects during CISB.…”
mentioning
confidence: 99%